Women that fight: The female participation in mixed martial arts events - Lisiane Caroline Rodrigues Hermes (FUCAPE Business School, 2016)
Sports marketing is in Mixed Martial Arts (MMA) a strategic potential, either through the promotion and implementation of events or the interested in sports. Thus, the management of the sports event planning becomes strategic to measure it considers the participation of female athletes in MMA events. This study aims to analyze the participation of females in MMA events, highlighting the perception of the fighters on the current business scenario in this segment. The method is configured as an exploratory and descriptive research with a qualitative approach, where there is information content analysis obtained through an open questionnaire. The results showed that the MMA product planning females is working strategically towards attracting viewers and brand awareness. In addition, further notes to male dominance in this type of sport, emphasizing gender issues related to compensation of the athletes and their occupation. However, it is clear that athletes even challenged by this scenario, remain convinced of their choices by segment.